Does nivolumab for progressed metastatic lung cancer fulfill its promises? An efficacy and safety analysis in 20 general hospitals. (January 2018) - Tournoy, Kurt G.; Thomeer, Michiel; Germonpré, Paul; Derijcke, Sofie; De Pauw, Rebecca; Galdermans, Daniëlla; Govaert, Karl; Govaerts, Elke; Schildermans, Rob; Declercq, Isabelle; De Brucker, Nele; Pat, Karin; et al.
Highlights: Nivolumab is prescribed to a heavily pretreated lung cancer patients, with many in ECOG 2. The median overall survival is inferior to what was published in the randomized phase III trials. An ECOG score 2 and the presence of liver metastasis strongly correlates with a worse survival. Many serious adverse events were reported supporting the need for a close follow-up. Abstract: Objectives: In patients with refractory or recurrent non-small-cell lung cancer (NSCLC) after first line chemotherapy, phase III trials showed superiority of nivolumab, an IgG4 programmed death-1 immune-checkpoint-inhibitor antibody, over docetaxel. We evaluated case mix, effectiveness and safety of nivolumab upon implementation in general practice. Materials and methods: In 20 general hospitals, all consecutive NSCLC patients treated with nivolumab within the medical need program (inclusion period 12 months) in Flanders − Belgium were evaluated. Results: There were 267 patients, Eastern Cooperative Oncology Group (ECOG) score was 2 in 24% and 0–1 in 76%. In 48%, two or more systemic regimens were given before nivolumab. The median overall survival was 7.8 months (95% confidence interval (CI) 6.3–9.3). At one year, the overall survival rate was 36.5 ± 0.34%. Median progression-free survival was 3.7 months (95% CI 2.9–4.5). An objective response was obtained in 23.2%. ECOG score 2 and presence of liver metastasis strongly correlated with worse survival (p < 0.00001). Treatment related adverse events grade 3 or 4 were reported in 21%, colitis (4%) and pneumonitis (7%) were most frequent. Conclusion: Upon implementation of nivolumab therapy in general hospitals, the case mix was characterized by a more heavily pretreated population with a substantial fraction of patients with ECOG score 2. The median overall survival is slightly inferior to what was published in the randomized phase III trials. An ECOG score 2 and the presence of liver metastasis correlated strongly with a worse survival. We report a high prevalence of serious adverse events.